(untitled) (Palíndromo, 2022)
This article correlates art, aesthetics and market, investigating how the changes in this relationship affect art education and teaching work. The objective is to highlight the strategies of capitalism in the construction of consensus, one of these strategies being the erasure of the specificity of art, in order to promote its insepa-rability from human work. The research reiterates the essence of relations and the production of more-value from the principles of historical-dialectical materialism and marks the theoretical awareness as a prerequisite for aesthetic fruition, valuing artistic knowledge as fundamental to human achievements. The methodologi-cal approach is based on the analysis of bibliographic studies, showing how the unveiling of the correlation between the areas implies an interpretive gain in the reading of reality and its consequences.